Pencegahan Hama Kera sebagai Upaya Mengatasi Permasalahan Petani Alpukat Desa Sumberahayu - Rr Nirmala Hapsari Dewi; Arneta Mayandha Ariyani; Ridwan Cahyo Widodo; Elsa Septiani Rintho Miharjo; Akhmad Mutohhar; Farida Nursyahidah (Yayasan Keluarga Guru Mandiri, 2023)
Avocado farming in Sumberahayu Village, Kendal Regency, holds great potential to be the primary source of income for the local community. However, the main challenge faced by avocado farmers is the attack of wildlife pests such as monkeys and wild boars, which threaten their harvest and livelihoods. Author has launched a program for the socialization of pest prevention. This program aims to provide better understanding and knowledge to avocado farmers on how to tackle the issue of wildlife pest infestations. The implementation method of the program includes problem identification, target audience analysis, development of socialization materials, selection of media and socialization methods, collaboration with relevant stakeholders, scheduling and location determination for socialization events, the actual execution of socialization activities, evaluation and feedback collection, and follow-up actions. Program can impact significantly benefit avocado farmers in Sumberahayu Village by helping to reduce losses caused by wildlife pest attacks and improving the sustainability of avocado farming in the region. This program also reflects the importance of collaboration between the academic world, student organizations, and the local community in addressing agricultural challenges at the grassroots level.